Language Patterns and Behaviour of the Peer Supporters in Multilingual Healthcare Conversational Forums - Mondal, Ishani; Bali, Kalika; Jain, Mohit; Choudhury, Monojit; Ronen, Keshet; Ochieng, Millicent; Awori, Kagonya; O'Neill, Jacki (LREC, 2022)
In this work, we conduct a quantitative linguistic analysis of the language usage patterns of multilingual peer supporters in two health-focused WhatsApp groups in Kenya comprising of youth living with HIV. Even though the language of communication for the group was predominantly English, we observe frequent use of Kiswahili, Sheng and code-mixing among the three languages. We present an analysis of language choice and its accommodation, different functions of code-mixing, and relationship between sentiment and code-mixing. To explore the effectiveness of off-the-shelf Language Technologies (LT) in such situations, we attempt to build a sentiment analyzer for this dataset. Our experiments demonstrate the challenges of developing LT and therefore effective interventions for such forums and languages. We provide recommendations for language resources that should be built to address these challenges.